Epididymis microlithiasis and semen abnormalities in young adult kidney transplant recipients. (6th November 2012) - Bozzini, G.; Lunelli, L.; Berlingheri, M.; Groppali, E.; Carmignani, L.
Summary: Microlithiasis of the epididymis is a rare ultrasound finding in the general population, but the incidence of calcifications in various organs of patients with end‐stage renal disease (ESRD) is extremely high. The aim of this study was to describe epididymal microlithiasis in 22 previously dialysed patients who received kidney transplantations at a median age of 19 years (range 9–30). The patients underwent scrotum ultrasonography, semen analysis and laboratory tests (renal function, sexual hormones, Ca, P and PTH) and were administered the International Index of Erectile Function questionnaire. Seventeen presented calcifications of the epididymis, two of whom had concomitant testicular calcifications; a further three patients had isolated testicular calcifications without epididymis involvement. It was not possible to investigate the fertility of all of the patients but 12 of the 13 whose semen was analysed showed abnormalities: five were azoospermic and seven oligospermic with various degrees of morphological anomalies. To the best of our knowledge, these are the first published data concerning the prevalence of epididymal calcifications in young dialysed patients undergoing renal transplantation. Epididymal microlithiasis and infertility were common findings and so performing a spermiogram and preserving semen before ESRD for future paternity may be good advice in this selected population.